2007
DOI: 10.1097/blo.0b013e31811f39fa
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Melatonin Signaling Dysfunction in Adolescent Idiopathic Scoliosis

Abstract: Presently, the genetic cause of adolescent idiopathic scoliosis (AIS), the most common form of scoliosis, remains unclear. Among many hypotheses, the neuroendocrine hypothesis involving a melatonin deficiency as the source for AIS generated the greatest interest and controversy since no decrease in circulating melatonin level has been observed in a majority of studies. Previously, we have reconciled the role of melatonin in AIS by demonstrating a melatonin signaling dysfunction occurring in osteoblasts derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 28 publications
6
68
0
3
Order By: Relevance
“…However, polymorphisms in melatonin receptor 1B have been associated with the occurrence of idiopathic scoliosis [46,47]. Furthermore, it has been demonstrated that melatonin stimulation of AIS osteoblasts results in differential phosphorylation of the G inhibitory signalling proteins that are coupled to the melatonin receptors, compared with normal osteoblasts [3].…”
Section: Intrinsic Factors Of the Ais Spinal Musculoskeletal System Smentioning
confidence: 99%
“…However, polymorphisms in melatonin receptor 1B have been associated with the occurrence of idiopathic scoliosis [46,47]. Furthermore, it has been demonstrated that melatonin stimulation of AIS osteoblasts results in differential phosphorylation of the G inhibitory signalling proteins that are coupled to the melatonin receptors, compared with normal osteoblasts [3].…”
Section: Intrinsic Factors Of the Ais Spinal Musculoskeletal System Smentioning
confidence: 99%
“…However, the etiopathogeny is still unclear, largely due to its multifactorial origin (Weinstein et al, 2008). While a clear genetic basis is lacking so far (Miller, 2007), AIS is correlated in part with abnormal levels of tyrosine, sex and growth hormones, dysfunction of the melatonin-signaling pathway, and calcium-binding receptor protein calmodulin (Ahn et al, 2002;Moreau et al, 2004;Azeddine et al, 2007;Cheung et al, 2008). These biochemical abnormalities, however, might be more related to the progression rather than the origin of AIS (Kindsfater et al, 1994;Machida et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is hypothesized that adjustment of menarche age may contribute to predisposition and curve progression potential of idiopathic scoliosis. In addition, potential difference of menarche age compared with normal control population may be correlated with hormonal disturbance involving estrogen, melatonin, and leptin [5][6][7][8][9][10], thus contributing to abnormal pubertal growth, which may be responsible for curve onset and progression of AIS. Such hypothesis, first and foremost, warrants menstrual status data supportive of abnormal menarche age with respect to general population.…”
Section: Introductionmentioning
confidence: 99%